Imagining Language: An Anthology - Rasula, Jed; McCaffery, Steve (Cambridge, MA MIT Press, 1998)
When works such as Joyce's Finnegans Wake and Stein's Tender Buttons were first introduced, they went so far beyond prevailing linguistic standards that they were widely considered "unreadable," if not scandalous. Jed Rasula and Steve McCaffery take these and other examples of twentieth-century avant-garde writing as the starting point for a collection of writings that demonstrates a continuum of creative conjecture on language from antiquity to the present. The anthology, which spans three millennia, generally bypasses chronology in order to illuminate unexpected congruities between seemingly discordant materials. Together, the writings celebrate the scope and prodigality of linguistic speculation in the West going back to the pre-Socratics.
Keywords: Linguistics